TouchDevelop: Programming on the Go - Horspool, Nigel; Tillmann, Nikolai; Bishop, Judith (Microsoft research, 2013)
Nigel Horspool is a professor of computer science at the University of Victoria. His main focus for research and teaching has been programming languages and compilers. He is the author or co-author of three books, which cover the C language, Unix and the C# language. He is currently the co- editor of the journal Software: Practice and Experience . He has a PhD from the University of Toronto, Canada in Computer Science.